2016
DOI: 10.3390/antiox6010002
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea and Other Tea Polyphenols: Effects on Sebum Production and Acne Vulgaris

Abstract: Polyphenols are antioxidant molecules found in many foods including nuts, fruits, vegetables, chocolate, wine, and tea. Polyphenols have antimicrobial, anti-inflammatory, and antineoplastic properties. Recent studies suggest that tea polyphenols may be used for reducing sebum production in the skin and for treatment of acne vulgaris. This review examines the evidence for use of topically and orally ingested tea polyphenols against sebum production and for acne treatment and prevention. The PubMed database was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Even though this study reports recent epidemiological data about factors triggering acne, other factors, including diet, may be concomitantly responsible for the evolution of acne in the population studied, such as sugar added to beverages containing tea. Conversely, there is some evidence through level C studies that green tea polyphenols may be beneficial in reducing sebum secretion, while also showing some antimicrobial properties, thus being potentially beneficial in acne …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this study reports recent epidemiological data about factors triggering acne, other factors, including diet, may be concomitantly responsible for the evolution of acne in the population studied, such as sugar added to beverages containing tea. Conversely, there is some evidence through level C studies that green tea polyphenols may be beneficial in reducing sebum secretion, while also showing some antimicrobial properties, thus being potentially beneficial in acne …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, there is some evidence through level C studies that green tea polyphenols may be beneficial in reducing sebum secretion, while also showing some antimicrobial properties, thus being potentially beneficial in acne. 77,78 Vongraviopap and Asawanonda reported that 99% dark chocolate, when consumed in normal amounts for 4 weeks, exacerbated acne in male subjects with acne-prone skin, potentially due to the presence of saturated fatty acids. 79 A crossover, randomized, level B study of the impact of chocolate bars and jelly beans on the worsening or onset of acne showed that chocolate bar intake resulted in a worsening of acne.…”
Section: Nutrition Factors Potentially Impacting On Acnementioning
confidence: 99%
“…Recent studies suggest that tea polyphenols may be used for reducing sebum production in the skin and for treatment of AV. Again, green tea and green tea-lotus combination topicals could be used to treat skin diseases that are associated with increased sebum secretion, such as AV [163][164][165]. Apple polyphenols (APP) inhibited Dexamethasone-induced lipid production and expression of sterol response element-binding protein-1 and its target enzymes, acetyl-CoA carboxylase and fatty acid synthase, in the sebocytes.…”
Section: Acne Preventionmentioning
confidence: 99%
“…The Paleolithic diet, which emphasizes fruits, vegetables, grassfed meat, nuts, and healthy fats, has been suggested to be an ideal diet to prevent acne and help alleviate acne vulgaris in affected individuals [21,22]. Tea, a beverage commonly consumed worldwide, contains polyphenols, which are antioxidant molecules with antimicrobial and anti-inflammatory properties [23]. Some studies have suggested that tea polyphenols reduce overall sebum production and thus can help treat acne [23][24][25][26][27][28][29].…”
mentioning
confidence: 99%
“…Tea, a beverage commonly consumed worldwide, contains polyphenols, which are antioxidant molecules with antimicrobial and anti-inflammatory properties [23]. Some studies have suggested that tea polyphenols reduce overall sebum production and thus can help treat acne [23][24][25][26][27][28][29]. Compared to other types of tea, green tea has the highest polyphenolic content [30].…”
mentioning
confidence: 99%